Qualitatively and quantitatively different solvatochromism of the MLCT and MMCT absorption bands of centrosymmetric acceptor-bridged diiron (II, II) and diiron(III, II) cyanide complexes - Glöckle, Markus (2002)
The energies of the metal-to-ligand charge transfer (MLCT) and metal-to-metal charge transfer (MMCT) absorption bands of a number of heterocycle-bridged diiron(II, II) homovalent and diiron(III, II) mixed-valent complexes correlate linearly with Gutmann's acceptor number (AN). The compounds are (NEt4)6[(NC)5Fe(μ-tz)Fe(CN)5] and (NEt4)5[(NC)5Fe(μ-tz)Fe(CN)5], tz=1,2,4,5-tetrazine; (NEt4)4[(NC)4Fe(μ-bptz)Fe(CN) 4] and (NEt4)3[(NC)4Fe(μ-bptz)Fe(CN) 4], bptz=3,6-bis(2-pyridyl)-1,2,4,5-tetrazine; (NEt4)4[(NC)4Fe(μ-bmtz)Fe(CN) 4], bmtz=3,6-bis(2-pyrimidyl)-1,2,4,5-tetrazine; (NEt4)4[(NC)4Fe(μ-bpym)Fe(CN) 4], bpym=2,2′-bipyrimidine. Mononuclear analogues of the tz and bpym ligands were also studied. Various degrees of negative and positive solvatochromism are observed for centrosymmetric dinuclear systems. Unusual observations include the large negative solvatochromism of MLCT bands in Fe(II)Fe(II) species lacking a permanent dipole moment, the positive solvatochromism of MLCT/LMCT bands and the small negative solvatochromism of MMCT bands in the valence-averaged Fe2.5Fe2.5 systems.